CROWDSOURCING AS A TOOL FOR CHANGING THE TRADITIONAL MODEL OF RELATIONSHIPS BETWEEN BRANDS, RETAIL TRADE AND CONSUMERS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines in detail the essence of consumer crowdsourcing and describes the relationships that arise in this case. Based on the analysis of the scientific literature, a matrix of the ratio of the intensity of consumer crowdsourcing and consumer crowd-sending was built. There are four different states that the relationship between the consumer and the platform can have due to the construction of the matrix: special relationship, thorough partnership, stimulating relationship, natural partnership. The main indicators of consumer crowdsourcing platforms are characterized: main focus, key blocks, activity. Emphasized, that the primary focus of special relationships is on the brand's core product, and the relationships that emerge are characterized by cold loyalty as consumers focus on the utilitarian benefits of the platform, such as convenience or cost savings. While the main focus of natural partnership is on the identity project, the key blocks are the public, enthusiasm, benchmarking, and the activity is aimed at self-expansion plus self-enhancement. Examples of successful use of crowdsourcing in foreign practice are described. The areas of application of crowdsourcing in retail trade are determined: financing, marketplaces, design, technologies, delivery of goods. Detailed features of the application of crowdsourcing in such a direction as the delivery of goods. It was concluded that currently crowdsourcing cannot become an alternative to traditional trade, but it can provide additional opportunities, become an effective means of strengthening relations between brands, retail trade and consumers.
Keywords: consumer crowdsourcing, consumer crowdsourcing, natural partnership, retail, brand.